2017
DOI: 10.3389/fpls.2017.00366
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Mechanisms in the Evolution of Moss Defenses to Microbes

Abstract: Bryophytes, including mosses, liverworts and hornworts are early land plants that have evolved key adaptation mechanisms to cope with abiotic stresses and microorganisms. Microbial symbioses facilitated plant colonization of land by enhancing nutrient uptake leading to improved plant growth and fitness. In addition, early land plants acquired novel defense mechanisms to protect plant tissues from pre-existing microbial pathogens. Due to its evolutionary stage linking unicellular green algae to vascular plants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 123 publications
(245 reference statements)
3
37
0
Order By: Relevance
“…Terrestrial plants are thought to have evolved as the result of an ancient symbiosis between a semi-aquatic green alga and an aquatic fungus, borne onto land over 450 millennia ago [1]. In this model, the colonization of land by plants-and therefore their very evolution-was only possible through an intimate partnership with a filamentous microorganism [2][3][4].…”
Section: The Dawn Of Plant-microbe Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Terrestrial plants are thought to have evolved as the result of an ancient symbiosis between a semi-aquatic green alga and an aquatic fungus, borne onto land over 450 millennia ago [1]. In this model, the colonization of land by plants-and therefore their very evolution-was only possible through an intimate partnership with a filamentous microorganism [2][3][4].…”
Section: The Dawn Of Plant-microbe Interactionsmentioning
confidence: 99%
“…The rationale is that comparative studies with a range of land plants will shed light on ancestral features of plant-microbe interactions. It turns out that many microbial pathogens can infect bryophytes, causing disease symptoms such as necrosis and tissue maceration [2]. The oomycete Phytophthora palmivora was shown to colonize the photosynthetic layer of liverworts-the earliest diverging land plant-and to form intracellular hyphal structures similar to the haustoria produced on angiosperms [3] (Figure 1b).…”
Section: The Dawn Of Plant-microbe Interactionsmentioning
confidence: 99%
“…Generally, mosses are observed to lack fungal symbionts such as mycorrhizal fungi (Field et al, 2015), but studies during the last decade have consistently reported that they host rich fungal communities Currah, 2006, 2007;Stenroos et al, 2010;U'Ren et al, 2010U'Ren et al, , 2012. Despite the uncertainty about the phylogenetic relationships among bryophytes and their affiliations to tracheophytes (Puttick et al, 2018), fungal interactions with early diverging land plants could unveil ancestral genetic mechanisms associated with the origin of fungal endophytism (Delaux et al, 2013;Ponce de León and Montesano, 2017;Lutzoni et al, 2018). Perennial mosses can have a natural senescence gradient that is ideal to study the functions of fungal endophytes and their life cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, our understanding of plant-pathogen interactions in these plants is extremely limited. In comparison, several groups have described pathogenic interactions in the model moss Physcomitrella patens [21-23]. The colonization of moss tissues is associated with intracellular hyphal growth, however specialized infection structures similar to haustoria are not observed within moss cells [22].…”
Section: Introductionmentioning
confidence: 99%